The Impact Of Service Quality, Brand Image, And Social Media Marketing On The Purchase Decision At The Aryaduta Suites Semanggi Hotel Jakarta - Prasetyo, Eko; Nainggolan, Bonifasius MH (Jurnal Ekonomi, 2024)
This study will ascertain how social media marketing, brand image, and service quality influence guests' decisions to stay at the Aryaduta Suite Semanggi Hotel in Jakarta.  This research is a quantitative research by distributing questionnaires to hotel guests. The research sample is guests staying at the Aryaduta Suite Semanggi Hotel, Jakarta. The sampling technique uses a non-probability sampling technique, namely the accident sampling technique. The final sample of the study was 171 guests.  Multiple linear regression was used for data analysis, and SPSS version 26 software was used for data processing. The study's findings will demonstrate that, both partially and simultaneously, social media marketing, brand image, and service quality significantly influence visitors' decisions to stay in Hotel Aryaduta Suite Semanggi.